Localisation of Theiler's Murine Encephalomyelitis virus non-structural proteins 2B, 2C, 2BC and 3A in BHK-21 cells, and the effect of amino acid substitutions in 2C on localisation and virus replication - Murray, Lindsay (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 2007)
The picornavirus family includes significant human and animal viruses such as poliovirus (PV), human rhinovirus (HRV) and foot-and-mouth-disease virus (FMDV). Current disease treatment and control strategies are limited by an incomplete understanding of the interactions between the non-structural, replicative picornavirus proteins and host cell components. To investigate these interactions, Theiler's murine encephalomyelitis virus (TMEV) 2B, 2C, 2BC and 3A proteins were transiently expressed in BHK-21 cells and detected by indirect immunostaining and laser-scanning or epifluorescence microscopy. The signal of the 2B protein overlapped with that of the ER marker protein, ERp60, as well as that of the peripheral Golgi marker protein, Î²-COP. The 2C protein overlapped with ERp60 in a faint reticular stain, and localised to large punctate structures that partially overlapped with Î²-COP at higher levels of expression. The 2BC protein located to large perinuclear structures that overlapped exclusively with Î²-COP. The TMEV 3A protein signal overlapped with both ERp60 and Î²-COP stains, in addition in cells expressing the 3A protein the ER appeared swollen and bulbous while the Golgi was dispersed in some cells. 2C and 2BC proteins with C-terminal deletions localised in the same manner as the wild type proteins indicating that the localisation signals that determine subcellular localisation of the proteins are within the N-terminal 60 amino acids of the 2C protein. The significance of the high degree of conservation of the N-terminal domain of the 2C protein throughout the Picornaviridae was investigated through the introduction of amino acid substitution mutations at highly conserved residues in the N-terminal domain of 2C into the viral cDNA. Upon transfection of the viral RNA into BHK-21 cells, it was observed that substitution of amino acid residues 8, 18 and 29 abolished the ability of TMEV to induce cytopathic effect (CPE), while substitution of residues 4, 14 and 23 only attenuated the ability of TMEV to induce CPE. To determine whether amino acid substitution mutations would affect the localisation of the 2C protein, 2C proteins with substitution mutations at amino acids 4, 8, 14, 18, 23 and 29 were transiently expressed in BHK-21 cells and detected by indirect imrnunostaining and examination by laser-scanning confocal and epifluorescence microscopy. The 2C mutant 4, 8 and 29 proteins showed slightly altered localisation patterns compared to the wild type protein with a significant portion of the proteins localising in a perinuclear stain suggesting possible localisation to the nuclear envelop. The 2C mutant 14 and 18 proteins localised to a diffuse pattern in BHK-21 cells while the 2C mutant 23 protein located to small punctate structures that partially overlapped with the ERp60 stain but were completely separate from the Î²-COP stain. Finally, a hydrophilic, antigenic region of the 2C protein was expressed in frame with an N-terminal GST tag and was successfully purified on a pilot-scale and detected by Western analysis. This 2C178 peptide will be used to generate antibodies against the 2C and 2BC proteins for use in future studies. This study has furthered our knowledge of the localisation of the picornavirus 2B, 2C, 2BC and 3A proteins in host cells and identified a possible link between this localisation and an ability of TMEV to replicate in BHK-21 cells.
Keywords: Encephalomyelitis -- Genetic aspects; Amino acid sequence; Picornaviruses; Viruses -- Reproduction